Projetos de nação e dilemas de identidade em Cabo Verde (1975-1992) - Pereira, Ratsiferana Macrina Alfama (2016)
This research has as the theme ,the Cape Verdean Nation and to analyze the multifaceted process of building national projects in Cape Verde in the 1980-1992 period, taking into account the issues of identity, constitutional and human rights. The Cape Verde Islands in the Atlantic Ocean have been populated since the fifteenth century, for two people, two races, two different cultures (African and European) and seek, even in this century, an identity consensus "imagined community". So many identity elements are aimed to define "what is to be Cape Verde". Based on qualitative research literature, historical and documentary, we seek to maintain our expertise in theoretical and methodological frameworks explicit, it is not our intention to achieve absolute truths, but rather contribute to the construction of a new synthesis with new reflections on the content of issue national identity. The corpus of the research focuses on the national symbols of two specific moments in recent history Cape Verdean, African approaches (1975-1980) and European approaches (1990-1992) as well as the political perspectives of two intellectuals such period, Aristides Pereira (African time) and Carlos Veiga (European time). The theoretical references to the ongoing work coalesce around the reflections of Benedict Anderson, Stuart Hall and Charles Taylor searching the nation, identity and multiculturalism. It is considered as advocated hypothesis, that the identity, constitutional and human rights are "territories" of political dispute in the "imagined projects."